Hybrid arch-forepoling synergy for construction-stage deformation control in shallow swelling soft-rock tunnels under asymmetric loading - Duo Zhang; Qingtong Jin; Haining Hao; Yu Zhang; Huasheng Zhang (European Journal of Environmental and Civil Engineering, 2026)

MYC-SEPT11 Axis Promotes osteoblast differentiation and bone formation via PI3K/AKT and RhoA/ROCK signaling pathways - Yiwen Zhao; Zhenghuan Zhu; Haining Chen; Yu Song; Feng Wang; Zhihui Huang; Wenming Ma; Wenge Ding; Jinbo Liu (Functional & Integrative Genomics, 2026)

Interlocking architecture-enabled ultrasensitive iontronic pressure sensor based on [BMIM]BF4-functionalized sponge - Xiaohui Guo; Xiaomeng Yao; Bing Hu; Xinran He; Hongtao Tan; Yaqi Yu; Haining Wang; Jiashu Cao; Zhiyuan Liu; Zhangling Duan; Ting-Jung Lin; Yunong Zhao (Chemical Engineering Journal, 2026)

Green-synthesized wood-polyacrylic acid composite hydrogel with in-situ incorporated silver nanoparticles for antibacterial treatment of oral ulcers - Yuchen Jiang; Chen Zeng; Qihua Li; Jianfeng Li; Yu Fang; Jingya Song; Haining Yu; Zixuan Yuan; Ruili Wang; Shaowu Pan; Weiqing Kong; Meifang Zhu (Chemical Engineering Journal, 2026)

Dense packing of hydrogen-bonding arrays enables high-strength, tough and multifunctional thermoplastic poly(urethane urea) elastomers - Xianwei Zhao; Azhu Wang; Jun Yu; Yuzhe Wang; Zengye Wang; Pei Li; Huaxia Wang; Huicong Liu; Haining Chen; Weiping Li (Chemical Engineering Journal, 2026)

Overburden Fracture Evolution and Surface Subsidence in Peak-Cluster Karst Longwall Mining A Physics-Constrained Multimodal Prediction Framework - Duo Zhang; Qingtong Jin; Haining Hao; Yu Zhang; Huasheng Zhang (Rock Mechanics and Rock Engineering, 2026)

Integrated experimental and network pharmacology analyses reveal inhibitory effects of albiflorin on renal cell carcinoma cells - Kai Meng; Yu Zhang; Lu Ma; Zixuan Chen; Haining Qian; Zongrun Sun; Xing Jia; Min Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Q-CLASS: an observation-based reconstruction dataset for streamflow at China’s large dam sites - Jiamiao Yu; Kaiwen Wang; Yuqi Li; Xinyu Li; Haining Jiang; Qiuyu Luo; Changming Liu; Xiaomang Liu (Journal of Hydrology, 2026)

Attribution of interannual runoff magnitude and variability in China’s large reservoir drainage areas using Global Hydrological Models - Xinyu Li; Kaiwen Wang; Qiuyu Luo; Guan Wang; Yu Lu; Haining Jiang; Jiamiao Yu; Changming Liu; Xiaomang Liu (Journal of Hydrology, 2026)

The extracellular polymeric substances and plants drive soil structural reinforcement and water retention in ground fissures - Haining Yu; Yinli Bi; Kaiwei Xu; Suping Peng; Yang Zhou; Yinchu Qiao (Rhizosphere, 2026)

Mechanisms of D‑tetramethrin‑induced neurotoxicity and locomotor abnormalities in zebrafish embryos revealed by transcriptomic analysis - Yuanhai Xie; Yunlong Meng; Yu Chen; Kangyu Liu; Lirong Huang; Xingkun Tang; Haining Li; Jianjun Chen; Zilin Zhong (Journal of Hazardous Materials, 2026)

Construction of superhydrophobic CoZnAl-LDH coating on anodized aluminum surfaces to enhance corrosion and wear resistance - Guixiang Wang; Qizi Wu; Maomao Guo; Shilong Zhang; Qiuyan Luo; Hao Yu; Xuyan Guo; Fuqiu Ma; Haining Feng; Ruizhi Wu; Boris Krit (Applied Clay Science, 2026)

Sustainable nutrient removal and biomass production in a self-permeation microalgae biofilm system with mechanistic and life cycle perspectives - Kaiwei Xu; Haining Yu; Zihan Zhu; Zhou Shen; Xiaotong Zou (Journal of Environmental Chemical Engineering, 2025)

Melatonin alleviates sodium sulfite-induced osteoporosis in mice via suppression of the ferroptosis pathway - Qiuping He; Lei Xie; Haining Peng; Xiao Xiao; Tengbo Yu (Apoptosis, 2025)
Sodium sulfite (SS) is a common food additive that is widely absorbed and distributed throughout the body, but its excessive intake has been linked to adverse health effects. Here, we investigate the impact of chronic SS exposure on bone tissue and the underlying mechanisms. Using a mouse model, we demonstrate that prolonged SS exposure induces significant bone loss, which correlates with alterations in ferroptosis-related markers. In vitro, SS exposure activates ferroptosis, which is characterized by elevated reactive oxygen species levels and impaired osteogenic differentiation in MC3T3 cells. Notably, melatonin, a potent endogenous antioxidant, mitigates SS-induced oxidative stress, inhibits ferroptosis, restores osteoblast function, and alleviates bone loss in mice. These findings highlight ferroptosis as a critical contributor to SS-induced osteoporosis and identify melatonin as a promising therapeutic agent for its prevention and treatment.

Effectiveness of mindfulness-based interventions on inflammaging: a systematic review and meta-analysis - Xiaohong Huang; Jing Lv; Dongxu Zhu; Haining Peng; Tengbo Yu (Biogerontology, 2025)

Optimized Deployment of Generalized OCDM in Deep-Sea Shadow-Zone Underwater Acoustic Channels - Haodong Yu; Cheng Chi; Yongxing Fan; Zhanqing Pu; Wei Wang; Li Yin; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2025)
Communication in deep-sea shadow zones remains a significant challenge due to high propagation losses, complex multipath effects, long transmission delays, and strong environmental influences. In recent years, orthogonal chirp division multiplexing (OCDM) has demonstrated promising performance in underwater acoustic communication due to its robustness against multipath interference. However, its high peak-to-average power ratio (PAPR) limits its reliability and efficiency in deep-sea shadow-zone environments. This study applies a recently proposed generalized orthogonal chirp division multiplexing (GOCDM) modulation scheme to deep-sea shadow-zone communication. GOCDM follows the same principles as orthogonal signal division multiplexing (OSDM) while offering the advantage of a reduced PAPR. By segmenting the data signal into multiple vector blocks, GOCDM enables flexible resource allocation, optimizing the PAPR without compromising performance. Theoretical analysis and practical simulations confirm that GOCDM preserves the full frequency diversity benefits of traditional OCDM, while mitigating PARR-related limitations. Additionally, deep-sea experiments were carried out to evaluate the practical performance of GOCDM in shadow-zone environments. The experimental results demonstrate that GOCDM achieves superior performance under low signal-to-noise ratio (SNR) conditions, where the system attains a 0 bit error rate (BER) at 4.2 dB and 6.8 dB, making it a promising solution for enhancing underwater acoustic communication in challenging deep-sea environments.

Development of a throttling venting model for CO2 pipelines and study of venting characteristics - Yifan He; Shuai Yu; Xingqing Yan; Jiaran An; Zhenning Fan; Haining Liang; Jianliang Yu (Process Safety and Environmental Protection, 2025)

Rational construction of 2D/2D Ti3C2/BiOBr S-scheme heterojunction for the boosted photo-degradation of 4-dodecylmorpholine under visible light irradiation - Yuqin Cai; Yuelin Wei; Jiaxin Chen; Shuhong Lv; Deguang Wu; Yunfang Huang; Xuefeng Yu; Haining Liu; Leqing Fan; Jihuai Wu (Journal of Environmental Chemical Engineering, 2025)

Prediction of microalgae harvesting efficiency and identification of important parameters for ballasted flotation using an optimized machine learning model - Kaiwei Xu; Zihan Zhu; Haining Yu; Xiaotong Zou (Algal Research, 2025)

Structural characteristics of areca nut seed neutral polysaccharide and its impact on gut microbiota from human feces - Mengfan Zhang; Haining Zhuang; Xiaowei Zhang; Xiaoyu Wang; Xia Fu; Sheng Chen; Lingyun Yao; Huatian Wang; Min Sun; Chuang Yu; Heng Yue; Tao Feng (Food Hydrocolloids, 2025)

Effects of complex polysaccharides by Ficus carica Linn. polysaccharide and peach gum on the development and metabolites of human gut microbiota - Bing Xu; Tao Feng; Shiqing Song; Huatian Wang; Lingyun Yao; Haining Zhuang; Xiaowei Zhang; Qian Liu; Chuang Yu; Min Sun (Food Hydrocolloids, 2024)

Butylparaben induces glycolipid metabolic disorders in mice via disruption of gut microbiota and FXR signaling - Haining Du; Lili Cui; Xinyi Zhao; Ziteng Yu; Tianyue He; Boya Zhang; Xingpei Fan; Meimei Zhao; Ruijiao Zhu; Ziyi Zhang; Mengcong Li; Jiaxin Li; et al. (Journal of Hazardous Materials, 2024)

Insight into in situ grown Ru-based integrated electrodes for hydrogen evolution reaction: Boosted mass transfer efficiency and promoted intrinsic activity - Di Wang; Wen Liu; Haining Wang; Shanfu Lu; Yunqi Li; Liang Luo; Linfeng Yu; Yan Xiang (Chemical Engineering Journal, 2024)

Dynamic regulation and cofactor engineering of escherichia coli to enhance production of glycolate from corn stover hydrolysate - Haining Yang; Yucai He; Shenghu Zhou; Yu Deng (Bioresource Technology, 2024)

Digestion under saliva, simulated gastric and small intestinal conditions and fermentation in vitro by human gut microbiota of polysaccharides from Ficus carica Linn. - Bing Xu; Shiqing Song; Lingyun Yao; Huatian Wang; Min Sun; Haining Zhuang; Xiaowei Zhang; Qian Liu; Chuang Yu; Tao Feng (Food Hydrocolloids, 2024)

Dual responsive cellulose-based fluorescent material fabricated in a CO2 switchable solvent for multifunctional applications - Yiting Xu; Xiaobo Yu; Meiling Chen; Yi Sun; Wei Zhang; Yajin Fang; Lanyun Fang; Haining Na; Fei Liu; Jin Zhu (Chemical Engineering Journal, 2023)

Serum organophosphate flame retardants and plasticizers in Chinese females of childbearing age: Association with serum reproductive and thyroid hormones - Yarui Liu; Yongcheng Li; Nan Xiao; Min Liu; Yu Wang; Haining Luo; Yiming Yao; Yujie Feng; Shuo Wang (Chemosphere, 2023)

Simulation of Oil Spills in Inland Rivers - Chenyang Kang; Haining Yang; Guyi Yu; Jian Deng; Yaqing Shu (Journal of Marine Science and Engineering, 2023)
The shipping volume in inland waterways has been rapidly increasing in recent years. However, it is still challenging to trace oil spills caused by maritime accidents. In this study, the oil spill dispersion trajectory in inland rivers was obtained by simulating the trajectory of oil particles under different waterway conditions based on a simulated flow field. Firstly, the flow field was simulated using a volume of fluid (VOF) model and the solution of an open-channel equation. Then, an oil particle diffusion and drift model was established using Python to simulate the diffusion of the oil. Finally, eight oil spill simulation scenarios were conducted with different channel shapes and cross-sections. The results showed that oil spills spread more extensively in a curved channel with a trapezoidal cross-section compared to other channel shapes and cross-sections. The findings of this research could be used to guide inland river environmental protection and oil spill trajectory tracking.

Synergistic effects of pH shift and heat treatment on solubility, physicochemical and structural properties, and lysinoalanine formation in silkworm pupa protein isolates - Haining Xu; Jiayin Pan; Mokhtar Dabbour; Benjamin Kumah Mintah; Wen Chen; Fan Yang; Zhaoli Zhang; Yu Cheng; Chunhua Dai; Ronghai He; Haile Ma (Food Research International, 2023)

Variational Bayesian Inference Time Delay Estimation for Passive Sonars - Feilong Ding; Cheng Chi; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2023)
In passive sonars, distance and depth estimation of underwater targets is often limited by the accuracy of time delay estimations. The estimation accuracy of the existing methods of time delay estimation is limited by the uniform discrete grid (signal sampling rate). When a true time delay is out of the grid, the estimation accuracy deteriorates due to the mismatch between the real-time delay and the discrete grid. This paper proposes a new method for time delay estimation, which realizes the time delay estimation under the framework of variational Bayesian inference. The proposed method is grid-less, that is, continuous in the time domain. Unlike the popular grid-less compressive time delay estimation method, this method does not require parameter adjustment, and can automatically estimate the number of time delays, noise variance, and amplitude variance. The simulation results showed that the performance of the proposed method was superior to the reference state-of-the-art time delay estimation methods.

Waveform Design Using Coprime Frequency-Modulated Pulse Trains for Reverberation Suppression of Active Sonar - Xiaobin Cui; Cheng Chi; Shuqiu Li; Zigao Li; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2022)
Over the last two decades, low-frequency active sonar has become an attractive tool for underwater target detection. The reverberation to signal ratio (RSR) of transmitted waveforms is an important factor affecting the detection capability of low-frequency active sonar. Therefore, reasonable waveform design for reverberation suppression of active sonar is an important topic. Pulse trains of linear frequency-modulated (PTFM) waveforms have been proposed and manifested their good performance in suppressing reverberation. The number of sub-pulses is positively related to the reverberation to signal ratio; the lower the number of sub-pulses, the lower the reverberation to signal ratio. However, to avoid ambiguity in a Doppler measurement, the PTFM waveforms have a requirement for the number of sub-pulses to be satisfied, which prevents its reverberation suppression performance from being further improved. In this paper, we propose a coprime pulse train of linear frequency-modulated (CPTFM) waveform, which reduces the number of sub-pulses to some extent. Therefore, the ability of reverberation suppression of the CPTFM waveform can be improved. The RSR was chosen as the metric to evaluate the waveform’s ability to suppress reverberation, and the theoretical formula for the RSR of the CPTFM waveform was derived in zone A and B. With the overlap of zones A and B brought about by the decrease in the number of sub-pulses, the average RSR of zones A and B is used in this paper to evaluate the reverberation suppression ability of the waveform. The simulation experiment shows that the proposed CPTFM waveform decreases the average RSR by 7 dB and 20 dB in comparison to the reference PTFM waveform and continuous waveform (CW), which is consistent with the theoretical results by the derived formulas.

Underwater Tone Detection with Robust Coherently-Averaged Power Processor - Qichen Xie; Cheng Chi; Shenglong Jin; Guanqun Wang; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2022)
The detection of tonal signals with unknown frequencies is an important area of study in underwater signal processing. A common approach to address this issue is to use the Discrete Fourier Transform (DFT) for observations. When a tone does not lie precisely at the discrete DFT frequency point, its energy will leak to adjacent frequency point. This phenomenon is known as scalloping loss or Picket Fence Effect (PFE). PFE leads to the degradation of detection performance based on DFT. This paper studies the problem of robust detection in the case of PFE. A coherently-averaged power processor utilizing the information of adjacent frequency bins is designed. The results of simulations and experiments show that the proposed method is robust against PFE, and is highly suitable for tone detection in practical circumstances.

In vitro dual-target activities and in vivo antidiabetic effect of 3-hydroxy-N-(p-hydroxy-phenethyl) phthalimide in high-fat diet and streptozotocin-induced diabetic golden hamsters - Bin Xiao; Yunfeng Xiao; Haining Ning; Xiaoyan Han; Wenyan Li; Yuheng Ma; Na Zhao; Guanhua Du; Yu Dong; Jee H. Jung; Zhanfei She (Medicinal Chemistry Research, 2020)

Parametric Knocking Performance Investigation of Spark Ignition Natural Gas Engines and Dual Fuel Engines - La Xiang; Gerasimos Theotokatos; Haining Cui; Keda Xu; Hongkai Ben; Yu Ding (Journal of Marine Science and Engineering, 2020)
Both spark ignition (SI) natural gas engines and compression ignition (CI) dual fuel (DF) engines suffer from knocking when the unburnt mixture ignites spontaneously prior to the flame front arrival. In this study, a parametric investigation is performed on the knocking performance of these two engine types by using the GT-Power software. An SI natural gas engine and a DF engine are modelled by employing a two-zone zero-dimensional combustion model, which uses Wiebe function to determine the combustion rate and provides adequate prediction of the unburnt zone temperature, which is crucial for the knocking prediction. The developed models are validated against experimentally measured parameters and are subsequently used for performing parametric investigations. The derived results are analysed to quantify the effect of the compression ratio, air-fuel equivalence ratio and ignition timing on both engines as well as the effect of pilot fuel energy proportion on the DF engine. The results demonstrate that the compression ratio of the investigated SI and DF engines must be limited to 11 and 16.5, respectively, for avoiding knocking occurrence. The ignition timing for the SI and the DF engines must be controlled after −38°CA and 3°CA, respectively. A higher pilot fuel energy proportion between 5% and 15% results in increasing the knocking tendency and intensity for the DF Engine at high loads. This study results in better insights on the impacts of the investigated engine design and operating settings for natural gas (NG)-fuelled engines, thus it can provide useful support for obtaining the optimal settings targeting a desired combustion behaviour and engine performance while attenuating the knocking tendency.

Mechanism of Free Zn(2+) Enhancing Inhibitory Effects of EGCG on the Growth of PC-3 Cells: Interactions with Mitochondria - Junguo Yang; Haining Yu; Shili Sun; Lancui Zhang; Undurti N. Das; Hui Ruan; Guoqing He; Shengrong Shen (Biological Trace Element Research, 2009)